2023
DOI: 10.1111/jre.13186
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidin enhances the endogenous regeneration of alveolar bone by elevating the autophagy of PDLSCs

Zhuo Liu,
Qilin Li,
Xiangyao Wang
et al.

Abstract: ObjectiveThis study aimed to investigate the effect of proanthocyanidin (PA) on osteogenesis mediated by periodontal ligament stem cells (PDLSCs) and endogenous alveolar bone regeneration.BackgroundLeveraging the osteogenic potential of resident stem cells is a promising strategy for alveolar bone regeneration. PA has been reported to be effective in osteogenesis. However, the effect and mechanism of PA on the osteogenic differentiation of PDLSCs remain elusive.MethodsHuman PDLSCs were treated with various dos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…[ 282 ] In recent years, researchers found that medications, and especially host modulators, show great potential in resolving or inhibiting the periodontal inflammatory process, particularly in the early phases of periodontitis combined with non‐surgical periodontal treatment. [ 283 , 284 , 285 , 286 , 287 , 288 , 289 ] These host modulators include statins like atorvastatin, rosuvastatin, and simvastatin, as well as alendronate and metformin. [ 80 , 89 , 92 , 95 , 96 , 98 , 99 , 105 , 290 , 291 , 292 , 293 , 294 , 295 , 296 ] Statins exhibit anti‐inflammatory and immunomodulatory properties while inhibiting osteoclasts and stimulating bone morphogenetic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…[ 282 ] In recent years, researchers found that medications, and especially host modulators, show great potential in resolving or inhibiting the periodontal inflammatory process, particularly in the early phases of periodontitis combined with non‐surgical periodontal treatment. [ 283 , 284 , 285 , 286 , 287 , 288 , 289 ] These host modulators include statins like atorvastatin, rosuvastatin, and simvastatin, as well as alendronate and metformin. [ 80 , 89 , 92 , 95 , 96 , 98 , 99 , 105 , 290 , 291 , 292 , 293 , 294 , 295 , 296 ] Statins exhibit anti‐inflammatory and immunomodulatory properties while inhibiting osteoclasts and stimulating bone morphogenetic proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The association of FGF-2 with heparin significantly decreases the degradation of FGF-2 and greatly enhances its mitogenic activity. Additionally, heparin sulfate proteoglycans act as cofactors in the interactions between FGF2 and FGF receptors, facilitating the activation of downstream signaling pathways [55][56][57]. In general, clinical data substantiates the safety and effectiveness of employing FGF-2 in the treatment of intraosseous defects in periodontal conditions.…”
Section: Fibroblast-derived Growth Factor (Fgf)mentioning
confidence: 91%
“…This product incorporates β-tricalcium phosphate as a scaffold [50,51,55]. Residing within the ζ-granules of platelets and discharged upon activation, PDGF has been demonstrated to stimulate DNA synthesis, chemotaxis, and the synthesis of collagen and glycosaminoglycans in fibroblasts [56][57][58]. Laboratory analyses conducted in vitro have shown that PDGF significantly enhances the expression of stem cell markers and promotes the proliferation of mesenchymal stem cells (MSCs) isolated from PDL tissues [59].…”
Section: Platelet-derived Growth Factor (Pdgf)mentioning
confidence: 99%
“…Proanthocyanidins can promote osteogenic differentiation of human periodontal ligament cells in inflammatory environments by inhibiting the NF-κB signaling pathway [ 24 ]. Moreover, our recent study found that proanthocyanidins activate the autophagy of PDLSCs by inhibiting the PI3K/Akt/mTOR signaling pathway, thereby promoting osteogenesis and enhancing endogenous alveolar bone regeneration [ 25 ]. However, the specific mechanism by which proanthocyanidins promote the osteogenic differentiation of PDLSCs in the inflammatory state remains to be refined.…”
Section: Introductionmentioning
confidence: 99%